Does International Liquidity Matter For G-7 Countries? A PVAR Approach - Mesut Turkay (International Econometric Review (IER), 2018)
Global liquidity has been more and more important in the last couple of years and everbody from media to policymakers are talking about it. In order to shed light on the effects of global liquidity, we investigate the impact of global liquidity expansion on major macroeconomic variables of G-7 countries by using panel vector autoregressive (PVAR) model and four different global liquidity indicators. We find that our data is nonstationary, there is cross sectional dependence and no cointegration relationship exits. Impulse response results show that an increase in global liquidity lowers government bond yields and has limited effect on output, inflation and real exchange rate. Additionally, global liquidity explains up to 10 percent of the variation in government bond yields. Our model results imply that the impact of global liquidity on the macroeconomic variables of G-7 countries is not very striking as some other studies suggest.
Keywords: C33; E44; E51; E52; 330; Global Liquidity; Panel Vector Autoregressive; Impulse Response